2016
DOI: 10.1111/1471-0528.14248
|View full text |Cite
|
Sign up to set email alerts
|

Self‐administration of injectable contraceptives: a systematic review

Abstract: BackgroundThe contraceptive injectable is a safe and effective method that is used worldwide. With the variety of injectable delivery systems, there is potential for administration by the woman herself. Self‐administration of the contraceptive injectable is the subject of this systematic review.ObjectivesTo assess how effective and safe the contraceptive injectable method is when women themselves perform/administer it, compared with when the usual healthcare providers administer it.Search strategyWe searched P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…As of August, 2017, Sayana Press was registered for self-injection in 18 countries, including seven in sub-Saharan Africa (Radola A, Pfizer, personal communication). Proponents of self-injection cite the potential for improved contraceptive use due to increased timeliness of re-injection; 16 self-injection would also eliminate the barrier of having to visit the clinic or CHW. Indeed, previous research in high-income countries has shown that self-injection of DMPA-SC is feasible and safe.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…As of August, 2017, Sayana Press was registered for self-injection in 18 countries, including seven in sub-Saharan Africa (Radola A, Pfizer, personal communication). Proponents of self-injection cite the potential for improved contraceptive use due to increased timeliness of re-injection; 16 self-injection would also eliminate the barrier of having to visit the clinic or CHW. Indeed, previous research in high-income countries has shown that self-injection of DMPA-SC is feasible and safe.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…More than 40 million women worldwide use injectable contraceptives, and in many low-and middle-income country (LMIC) settings, injectables account for at least one half of modern contraceptive method use [1]. The subcutaneous formulation of depot medroxyprogesterone acetate (DMPA-SC) in the prefilled Uniject™ injection system, commercially known as Sayana® Press, is gaining popularity among family planning providers and women.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore unsurprising that self-injection at a time and place of their own choosing offers patients another level of convenience that they are keen to take advantage of. The available literature on self-injection highlights the convenience of this method (Kim et al, 2017; Cameron et al, 2012b).…”
Section: Licensing Of Sayana Press ® For Self-injectionmentioning
confidence: 99%